MyPyramid Message: Moderation - Claudia Peñuela; Karla P. Shelnutt (EDIS)
FCS8928, a 2-page handout by Claudia Peñuela and Karla P. Shelnutt, explains how moderation is represented in the MyPyramid symbol and provides guidelines for practicing moderation. Includes a review exercise and references. Published by the UF Department of Family, Youth and Community Sciences, October 2010.